Ecotopes and Herd Foraging Practices in the Steppe/Mountain Ecotone of Central Asia during the Bronze and Iron Ages. Issue Volume 33:Issues 1(2013) (March 2013) - Spengler, Robert N.; Frachetti, Michael D.; Fritz, Gayle J.
Eurasian mobile pastoralists living in semiarid environments focus on specific locations on the landscape where pasture resources and water are available. Ecotones –or intermediary zones between the mountain and steppe environments– create mosaic landscapes composed of forage-rich patches and other discrete enclaves of useful biota for pastoralist communities. Ecotopes (ecological patches) provide vital resources for the herding systems used in Central Asia today as well as in the past. We document and discuss wild seed composition of archaeobotanical samples from the Bronze and Iron Age site of Begash in southeastern Kazakhstan noting that much of the archaeobotanical assemblage represents carbonized animal dung, which is currently and historically used as fuel in this region by mobile pastoralists. The seeds offer a window into prehistoric herding patterns and provide a nuanced view of prehistoric land use, social interaction, and community formation across discrete ecological nodes in the Bronze and Iron Ages.